Symmetry and equivalence analysis of wave dynamics in continuous media: elastic rods, plates, and nonlinear solitonic structures - Nunes, Afonso Willian [UNESP] (Universidade Estadual Paulista (Unesp), 2025)
Wave analysis supports numerous contemporary engineering systems' optimal design, performance, and safety. Yet, several mathematical models essential for describing the physical phenomena these systems undergo are either difficult to tackle or have not yet been analytically investigated. As a result, such challenges are frequently bypassed in favor of standard numerical studies, overlooking valuable insights that analytical methods could provide when predicting the dynamics exhibited by these systems. This thesis focuses on employing analytical symmetry analysis to examine differential equations that arise from wave dynamics models in continuous media. Simpler, equivalent problems are derived, allowing for the computation of original exact mode shapes and traveling-wave solutions for non-uniform, functionally graded rods described by the elementary rod model. In addition, new complete sets of exact invariant solutions are found for the mode shape equation of rectangular Kirchhoff plates and the generalized Calogero–Bogoyavlenskii–Schiff equation for solitonic structures through the proposed symmetry-based perspective.

O estudo da dinâmica de ondas tem papel fundamental no design, desempenho e segurança de diversos sistemas de engenharia contemporâneos. No entanto, muitos modelos matemáticos úteis na descrição dos fenômenos físicos desses sistemas apresentam dificuldades de resolução ou ainda não foram investigados de maneira analítica. Como resultado, tais desafios frequentemente são deixados de lado em favor de estudos numéricos, o que pode levar à perda de noções valiosas fornecidas por métodos analíticos na predição de comportamentos dinâmicos. Esta tese apresenta investigações analíticas por meio de análises de simetria para examinar equações diferenciais provenientes da dinâmica de ondas em meios contínuos. Como resultado, surgem problemas equivalentes mais simples, permitindo a obtenção exata de modos de vibrar e soluções em termos de ondas viajantes para estruturas do tipo barra elementar com geometrias e propriedades materiais não constantes. Além disso, soluções invariantes exatas são determinadas para a equação dos modos de vibrar de placas de Kirchhoff retangulares e para a equação generalizada de Calogero–Bogoyavlenskii–Schiff da teoria de sólitons, analisando-as sob a perspectiva dos métodos de simetria.
Análise de simetria e equivalência em problemas de propagação de ondas em meios contínuos: barras elásticas, placas e estruturas solitônicas não lineares
Keywords: Symmetry analysis; Exact solutions; Elementary rods; Kirchhoff plates; Generalized Calogero–Bogoyavlenskii–Schiff equation; Análise de simetria; Soluções exatas; Barras elementares; Placas de Kirchhoff; Equação generalizada de Calogero–Bogoyavlenskii–Schiff